Pendidikan Moral Menurut Imam Al Ghazali dan Emile Durkheim serta Relevansinya terhadap Pendidikan Islam - Muhammad Farid Wajdi; Siti Soliyah (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2024)
This study aims to analyze the views of Imam Al Ghazali and Emile Durkheim on moral education and its relevance to Islamic education. The type of research uses a qualitative approach by conducting a literature review of the works of Imam Ghazali and Emile Durkheim related to moral education and other general references. The results show that moral education according to Imam Al Ghazali and Emile Durkheim has a strong relevance to Islamic education. Imam Al Ghazali's approach helps shape the moral character of individual Muslims through understanding ethical and spiritual values in Islam. While Emile Durkheim's approach helps build collective consciousness and solidarity in Muslim society. The implication of this study is that the concepts of moral education of Al Ghazali and Emile Durkheim can be applied in the context of Islamic education to enhance the formation of character and moral values of individual Muslims. Recommendations are given for the development of moral education in the context of Islamic education. including methods and strategies that can be used to integrate Islamic values in moral education and build the character of noble Muslim individuals.